Age and identity - Falkner, Clare (Milton Keynes : The Open University)
This program deals with the aspect of changing of identities and the process of aging
Series producer, Jeremy Cooper ; film editor, Anne Goudie
Narrator: Stuart Hall
Keywords: Health behavior -- Age factors; Identity (Psychology); Human reproduction -- Age factors